1/8 × 4

Rewrite it as

1/8 × 4/1

= (1×4)/(8×1)

= 4/8

= 1/2 teaspoon

1/8 × 4

Rewrite it as

1/8 × 4/1

= (1×4)/(8×1)

= 4/8

= 1/2 teaspoon

Something kind of kinky ☺

4/8 or 1/2 teaspoon.

Given root of polynomial function x=∛28

g(2)=x^{3} -28=0

Applying Newton's method

x_(n+1) = x_n - (g(x_n)) / (g'(x_n))

For c₁ ⇒ c₁ = c₀ - (g(c₀)) / (g'(c₀))

Thus, c₀ =3

So, g'(3)=27

g(3)=27-28=-1

c₁ = (3-(-1)) / (27) = (81+1) / (27)

c₁ = (82)/(27)

f(x) = 3x - 1

g(x) = 4x - 2

h(x) = 2f(x) + g(x)

h(x) = 2(3x - 1) + 4x - 2

= 6x -2 + 4x - 2

= 10x - 4

Use the chain rule with Fundamental Theorem of calculus

g′(x)=f(h(x)) h′(x) − f(ϕ(x)) ϕ′(x)

=f(x²) × d/dx (x²) − f(5x+1) × d/dx (5x+1)

= (sin x²)/(x²) × (2x) - (sin (5x+1))/(5x+1) × 5

= (2x sin x²)/(x²) - (-5 sin (5x+1))/(5x+1)

https://answers.yahoo.com/question/index?qid=20090424031100AAXjbJ0

I hope it'll help you.

To find 'c', solve f'(x)=0

⇒ (x² − 1) × 1 + 2x(x − 2) = 0

⇒ x²− 1 + 2x² − 4x = 0

⇒ 3x^{2} − 4x−1 = 0

It's a quadratic equation so, solve it using quadratic formula

⇒ [4±√16-(4)(3)(-1)] / (2(3))

⇒x = (2±√7)/(3)

⇒x = (2+√7)/(3) and x = (2-√7)/(3)

x = (2+ √7)/(3) = 1.55 ∈(1,2]

x … Read more

geometric return = ⁿ√{(1+r₁) × (1+r₂) × ...} - 1

Where, r = rate of return

n = number of periods

For 1st yr, rate of return = r₁ = 5% = 0.05

For 2nd yr, rate of return = r₂ = -30% = -0.3

Number of years = 2

geometric return = √{(1 + 0.05)(1 - 0.3)}-1= √{(1.05) (0.7)}-1= -0.143

Geometric … Read more

Let advance Tickets = A

door tickets = D

Make equations according to the problem

A + D = 120.....(1)

10A + 15D = $1390....(2)

Multiplying eq(1) by 10 and subtracting from eq(2) we get

D = 38(number of tichets at door)

Put value of D in eq(1) we get-

A + 38 = 120

A = 82(number of tichets were purchased in advance)

Bob is 20 years older than Ben. In 10 years, Bob will be twice as old as Ben. How old is each now?If Bob is 20 years older than Ben, then he was 20 years old when Ben was born.

If, in ten years, Bob will be twice as old as Ben, then we must consider … Read more

4y + 10 - 2y = 8 + y?Take the "y"s to one side.

4y - y + 10 -2y = 8

Simplify.

4y - 3y + 10 = 8

y + 10 = 8

Take the other numeric values to the opposite side to your unknown value.

y = 8 - 10

Simplify.

y = -2

⁸C₂ × ⁴C₁ + ⁸C₂ × ⁴C₂

= 28 × 4 + 28 × 6

= 280

cos A = -4/5

A = cos^-1 (-4/5)

A = 143°

tan (143/2) = 2.98

16 + (28/2) - (6 /10) - 4 × 2

Use order of operation, i.e., PEMDAS (Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction)

First, simplify parenthesis

= 16 + 14 - 0.6 - 4 × 2

Now, multiplication

= 16 + 14 - 0.6 - 8

Similarly, apply addition and subtraction

= 30 - 0.6 - 8

= 21.4

First you set these to naught. These=0 graph it.

not only popcorn but some steel glass is also have a same shape

Mathematics